Environment, society and economy of an early medieval river: the late Lombard and Carolingian Po Valley (northern Italy), 715-924 AD - Panato, Marco (2020)
This PhD thesis is focused on the different uses and meanings of rivers and freshwater for early medieval societies. It is based on a specific case study, the Po valley (northern Italy) between the eighth and the long ninth centuries AD. This period and geographical region have been mostly analysed by Italian and international historiography as it is one of the richest areas in term of documentary availability and has a complex socio-political and economic landscape very difficult to retrace in other parts of central and northern Europe. I have approached the analysis of this landscape starting from a natural element the river and its uses, highlighted its early medieval environmental patterns and used these to understand how these influenced the socio-economic trends of the period between the Lombard and the Carolingian dominations. My aims are in fact to reconstruct and analyse the ‘riverscape’ recognising how far it is possible to distinguish between specific characteristics linked to the different kingships that ruled northern Italy and more local patterns. In my research I conducted an interdisciplinary analysis between History and Archaeology, taking account also on the geoenvironmental data available for the landscape. This methodological approach brought to light a more complete spectrum of the riverscape highlighting different angles and perspectives. Finally it has been possible to a) achieve the complete reconstruction of the early medieval historical landscape, b) recognise the elements that characterised Lombard, Carolingian and local patterns along the river and its water, and c) recognise the circuits of men and goods that lived on the river and contributed to the formation of the Po valley riverscape.